Adoption of E-Commerce Technology Among Young Agro-Entrepreneurs in Coastal Manado: An Analysis Using the Technology Acceptance Model (TAM) - Tumiwa, Johan R.; Tuegeh, Octavia D. M. (Jurnal Agroekoteknologi Terapan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the agricultural sector of Manado’s coastal area are increasingly required to enhance their competitiveness by adopting information technology, particularly e-commerce. E-commerce adoption can improve efficiency, strengthen supply chain relationships, and lower operational costs for agro-entrepreneurs and young farmers, especially compared to traditional business methods. Young agro-entrepreneurs are believed to have a high level of technology acceptance, making them important drivers of digital transformation in coastal agriculture. This study aims to analyze the factors influencing e-commerce adoption among young agro-entrepreneurs in coastal Manado, using the Technology Acceptance Model (TAM) and Partial Least Squares Structural Equation Modeling (PLS-SEM). Stratified random sampling of 111 respondents revealed that computer self-efficacy significantly affects perceived ease of use. Both perceived usefulness and perceived ease of use significantly influence the attitude toward using e-commerce. Furthermore, attitude toward use has a significant impact on the behavioral intention to use e-commerce, which subsequently leads to actual usage. The findings suggest that e-commerce adoption among young agro-entrepreneurs can be further supported by enhancing digital skills, particularly in smartphone-based applications. Future research is recommended to explore the role of mobile technology self-efficacy in e-commerce adoption within agricultural MSMEs. Keywords: E-Commerce, MSMEs, TAM.